Exploring informal learning in higher education : a study in a technologically intense environment - Derwik, Pernilla (… pedagogiska inspirationskonferensen, 2025)
The study aims to investigate how students informally accomplish the acquisition of theoretical and practical knowledge in a technologically intense environment, and whether this accomplishment changes over a course. Furthermore, the study investigates the possible correlation to results. The study is based on a two-step survey conducted at the start and the end of a course in dynamic simulation. The sample consists of 40 students. The results are analyzed and presented based on two groups with different grade averages. The results show the likeliness of using various informal learning actions based on the identified groups. The results furthermore show how this likeliness develops over the course. Of significance, the results indicate that students that use informal learning actions as a strategy for acquiring knowledge might achieve higher grades. The results can be used to inform both students and teachers about the benefits of using informal learning actions in technology intense study environments. By highlighting such actions, students are made aware of additional opportunities to develop both their theoretical and practical knowledge of the topic at hand and not least improve their grades.